MEDIA DISCOURSE AND INTERNAL CONFLICT OF JAVANESE POWER IN YOGYAKARTA - Wulan, Roro Retno; Nugroho, Catur; Nastain, M. (Universitas Padjadjaran, 2023)
This paper attempts to reveal how the local media, Kedaulatan Rakyat, produces discourse on the Yogyakarta palace’s internal conflict involving Sri Sultan Hamengku Buwono X and his siblings. The Special Region of Yogyakarta as a province in Indonesia has a special government system that is different from other regions. The governor of Yogyakarta is not elected by the people like in other regions in Indonesia but is determined by the DPRD based on who serves as the King of the Yogyakarta Palace. This phenomenon becomes interesting when there are differences of opinion among the people and within the Yogyakarta Palace regarding the acceptance of women leaders. The conflict began to arise when Sultan Hamengku Buwono X issued the Sabda Tama and Sabda Raja (Sabda Raja) which were interpreted as the Sultan’s way to pave the way for his daughter to become heir to the throne. The Sultan’s younger siblings opposed the female king to rule in Yogyakarta, so an internal conflict arose. The research method used is a qualitative method with a critical discourse analysis approach using the Norman Fairclough model to analyze news texts related to the Yogyakarta Palace’s internal conflict from the Kedaulatan Rakyat Daily. From the results of the research, it was found that the Kedaulatan Rakyat Daily produced discourses on internal conflict in the Yogyakarta palace by representing the ideology and interests of Sultan HB X’s younger siblings. This local daily newspaper also commodified internal conflict in the Yogyakarta palace as events that were produced and disseminated to the public for the benefits media economy.